ANALISIS KEGAGALAN POMPA SENTRIFUGAL (OVERHUNG 212–P17) MENGGUNAKAN METODE FMEA DI PT KILANG PERTAMINA INTERNASIONAL RU II DUMAI - Yanel, Karnova; Safery, Rozi; Putra, Ismet Eka (Jurnal Teknologi dan Vokasi, 2025)
Centrifugal pumps are essential components in refinery processing systems, including those at PT Kilang Pertamina Internasional RU II Dumai. One of the pumps in operation, the overhung type 212–P17, has experienced a jammed condition affecting its performance. This study aims to analyze the potential failure modes of the pump components using the Failure Mode and Effect Analysis (FMEA) method and to determine corrective action priorities based on the Risk Priority Number (RPN). The analysis focused on four key factors: material integrity, shaft alignment, lubrication condition, and clearance. The results indicate that shaft misalignment had the highest RPN of 324, followed by lubrication failure with an RPN of 160. These findings suggest that corrective measures should prioritize shaft realignment and lubrication management. The FMEA approach has proven effective in identifying critical components and structuring a preventive maintenance strategy to enhance the operational reliability of the pump system.